Discussions on the Subjective Element of the Crime of Plunder in Comparison with German and Austrian Law - Hüsnü Sefa Eryıldız; Ali Boyracı (Ceza Hukuku ve Kriminoloji Dergisi)
Although the crime of plunder is considered to be a combined crime consisting of theft and coercion or the threat thereof in Turkish Criminal Law (regulated under Article 148 of the Turkish Criminal Code [TCC]), it is not specifically mentioned with regard to the aim of benefit. This choice of legislation has led to certain discussions about the subjective element of the crime of plunder and its scope of practice in doctrine. While the dissenting view considers the crime of plunder to be committable through general intent, the majority view and court practices consider that the perpetrator must act with the aim of benefit. Another controversial matter on the subjective element of the crime of plunder is how to identify the aim of benefit. Just as some claim that the aim of benefit includes both economic and immaterial benefits, others are also found who consider the aim of benefit to only involve economic benefits. This study examines the subjective element of the crime of plunder and the contents of the aim of benefit by comparing Turkish law with German and Austrian law while presenting the study’s resultant opinion.